Liuzhi Suojia Ecomuseum at Guizhou: Theater of Interaction and Negotiating Ethnic Minority Identities in China - Ruoyue, Kong; Singyabuth, Supachai; Wenli, Hu; Nina, Yang; Zhenzhen, Zhou (Journal of Cultural Analysis and Social Change, 2025)
This study employs qualitative research methods to examine the distinctive identity of the Miao people during the transformation of the Ecomuseum, with particular attention to how identity is represented within the Ecomuseum context and how it interacts with external audiences. The technical procedures adopted were bibliographic research and field research. The findings reveal that the everyday practices and rituals of the Longhorn Miao have become phenomena subject to observation, interpretation, and interaction by external visitors, shaping the maintenance and transmission of their unique identity. The Suojia Ecomuseum showcases the Suojia ethnic identity and serves as a performance space for self-presentation in interactions with outsiders. In this parallel context, cultural performance is no longer solely for the benefit of community life but are also designed to meet the expectations of outside observers. This parallel position creates a complex connection between Longhorn Miao, consumers, and other stakeholders, resulting in a continuous and dynamic process of negotiating the self-identities of the Miao people with outsiders.This research advances Ecomuseum studies by moving beyond heritage preservation narratives to emphasize the Ecomuseum as a contested arena of identity negotiation, cultural politics, and globalization.